Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.224
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating External Knowledge to Enhance Tabular Reasoning

Abstract: Reasoning about tabular information presents unique challenges to modern NLP approaches which largely rely on pre-trained contextualized embeddings of text. In this paper, we study these challenges through the problem of tabular natural language inference. We propose easy and effective modifications to how information is presented to a model for this task. We show via systematic experiments that these strategies substantially improve tabular inference performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Pre-training over semi-structured data Past work on pre-training over tables focused on reasoning over tables and knowledge-bases Yin et al, 2020;Herzig et al, 2020;Müller et al, 2021;Yu et al, 2021;Neeraja et al, 2021b) We evaluate our model, PReasM, on three reasoning-focused RC datasets and show that it leads to substantial improvements in all cases. Moreover, we thoroughly analyze the performance of PReasM and show that our approach dramatically improves performance on questions that require reasoning skills that were not acquired during the original pre-training, while maintaining comparable performance on other question types.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Pre-training over semi-structured data Past work on pre-training over tables focused on reasoning over tables and knowledge-bases Yin et al, 2020;Herzig et al, 2020;Müller et al, 2021;Yu et al, 2021;Neeraja et al, 2021b) We evaluate our model, PReasM, on three reasoning-focused RC datasets and show that it leads to substantial improvements in all cases. Moreover, we thoroughly analyze the performance of PReasM and show that our approach dramatically improves performance on questions that require reasoning skills that were not acquired during the original pre-training, while maintaining comparable performance on other question types.…”
Section: Related Workmentioning
confidence: 97%
“…We use tables from English Wikipedia 1 to generate D syn . English Wikipedia includes millions of tables with high lexical and domain diversity (Fetahu et al, 2019;Chen et al, 2020b;Gupta et al, 2020b;Talmor et al, 2021;Nan et al, 2021;Neeraja et al, 2021a). We first extract from Wikipedia all tables T that have at least two columns and 10-25 rows, resulting in more than 700K tables.…”
Section: Generating Examples From Tablesmentioning
confidence: 99%
“…To isolate rows from a premise table that are related to the hypothesis sentence, we apply Distracting Rows Removal (DRR), which was proposed by the previous approach (Neeraja et al, 2021). Since that approach was NN-based, a sentence vector representation was generated for each row in the table, and the original DRR was applied to the sentence representation.…”
Section: Rows Filteringmentioning
confidence: 99%
“…In recent years, modern neural network (NN) approaches have achieved high performance in many Natural Language Understanding benchmarks, such as BERT (Devlin et al, 2019). NNbased approaches (Neeraja et al, 2021) have also achieved high accuracy on the NLI task between semi-structured tables and texts, but previous studies have questioned whether NN-based models truly understand the various linguistic phenomena (Jia and Liang, 2017;Naik et al, 2018;Rozen et al, 2019;Ravichander et al, 2019;Richardson et al, 2020). These studies have shown that NN-based approaches have failed to achieve a high performance in numerical reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…IN-FOTABS (Gupta et al, 2020) and TABFACT focus on verifying a statement given a table from Wikipedia 1 as evidence. Neeraja et al (2021) propose simple modifications to how information is presented to existing textual models such as RoBERTa (Liu et al, 2019) to improve tabular fact verification. Along with releasing TABFACT, Chen et al (2020) also discuss two promising approaches for tabular fact verification, Latent Program Algorithm (LPA) and Table-BERT.…”
Section: Introductionmentioning
confidence: 99%